Immediate and long term evolution of valve replacement in children less than 12 years old - Atik,Fernando Antibas (1999)
OBJECTIVE: The aim of this work was the follow-up and evaluation of valve replacement in children under 12 years of age. METHODS: Forty-four children less than 12 years old were underwent valve replacement at INCOR-HCFMUSP between January 1986 and December 1992. Forty (91%) were rheumatic, 39 (88.7%) were in functional classes II or IV, 19 (43.2%) were operated upon on an emergency basis, and 6 (13.6%) had atrial fibrillation. Biological prostheses (BP) were employed in 26 patients (59.1%), and mechanical prostheses (MP) in 18 (40.9%). Mitral valves were replaced in 30 (68.7%), aortic valves in 8 (18.2%), a tricuspid valve in 1 (2.3%), and double (aortic and mitral) valves in 5 (11.4) of the patients. RESULTS: Hospital mortality was of 4.5% (2 cases). The mean follow-up period was 5.8 years. Re-operations occurred in 63.3% of the patients with BP and in 12.5% of those with MP (p=0.002). Infectious endocarditis was present in 26.3% of the BP, but in none of the cases of MP (p=0.049). Thrombosis occurred in 2 (12.5%) and hemorrhage in one (6.5%) of the patients with a MP. Delayed mortality occurred in 5 (11.9%) of the patients over a mean period of 2.6 years; four had had BP and one had a MP (NS). Actuarial survival and re-operation-free curves after 10 years were respectively, 82.5±7.7 (SD)% and 20.6±15.9%. CONCLUSION: Patients with MP required fewer re-operation, had less infectious endocarditis and lower late mortality rates compared with patients with bioprostheses. The former, therefore, appear to be the best valve replacement for pediatric patients.